The Effect of Using Smartphone toward The Quality of Sleep and the Impact on Learning Motivation Students - Sintiya Halisya Pebriani; Lily Marleni (University of Muhammadiyah Malang, 2020)
Introduction: Nowadays, using smartphone not only used to call and send a short message but used as tools multifunction such as browser, chatting, game, social media, and others. The using unlimited smartphone that caused by irregular sleep. Students who experienced poor quality of sleep will be influences their learning motivation in the class. Objective: The objective of this study to evaluate the direct effect and indirect effect of using smartphones toward learning motivation through the quality of sleep. Method: This study is a cross-sectional descriptive and verification design, with samples taken with a total sampling technique of 150 students. The data collection using questionnaires of using smartphones, sleep quality and learning motivation—the data analysis using path analysis. Results: Statistical analyses found that there was a direct effect using smartphones toward the quality of sleep was (p=0.001); there was a negative-direct effect of quality of sleep toward learning motivation (p=0.014). However, there was no direct effect using smartphones toward learning motivation (p= 0.686). Discussion: There was no direct effect of the use of smartphones toward learning motivation because there was an intervening variable of the quality of sleep; it means that there was an indirect effect using smartphones toward learning motivation through the quality of sleep.